From a Spatial Structure Perspective: Spatial‐Temporal Variation of Climate Redistribution of China Based on the Köppen–Geiger Classification - Yanlong Guan; Junguo Liu; Kai Wang; Wenfang Cao; Yelin Jiang; Hongwei Lu; Janne Heiskanen (Geophysical Research Letters)
Abstract Shifting climate zones are widely used to diagnose and predict regional climate change. However, few attempts have been made to measure the spatial redistribution of these climate zones from a spatial structure perspective. We investigated changes in spatial structure of Köppen climate landscape in China between 1963 and 2098 with a landscape aggregation index. Our results reveal an apparent signal from fragmentation to aggregation, accompanied by the intensification of areal dispersion between cold and warm climate types. Our attribution analysis indicates that anthropogenic forcings have a larger influence on changes of spatial structure than natural variation. We also found that topographical heterogeneity is likely to contribute to the regional spatial fragmentation, especially in the Qinghai‐Tibet Plateau. However, we also found that the spatial fragmentation will be weakened around the mid‐2040s. We argue that biodiversity is likely to be mediated by spatial structure of future climate landscapes in China.